Belonging and Unbelonging in Literary Geography: a Comparative Approach to Johann Koppelstätter’s and Arturo Manzini’s Place-based Detective Fiction - Nicola Gabellieri (Bollettino della Società Geografica Italiana)
The concept of a sense of belonging to a place has long been the subject of attention in geographical studies. Scholars have consistently highlighted the ability of literary works to convey a spatial sense of belonging on the part of protagonists and authors, as well as to foreground landscape elements that may reveal the characters’ personalities. Within this framework of research, the paper calls attention to the specular concept of estrangement, or unbelonging: a literary geographical quality that characterizes certain novels. A comparative analysis is presented between two different cycles of detective novels set in the Italian alpine areas. Specific elements of the landscape, the social milieu, and the authors’ psychology that might convey such a sense of belonging are identified and categorized. The analysis shows how the relationship between the protagonists and the space in a novel can be based on a sense of estrangement that plays a role in signifying the characters’ psychology and personality. In conclusion, it is proposed to consider the absence of the sense of belonging to place as a literary quality and element of agency within an intra-textual analysis of literary geography.